Representation theory of finite reductive groups - Cabanes, Marc, 1959- (New mathematical monographs, 2004)
Cabanes and Enguehard blend many of the main concerns of modern algebra, synthesising the past 25 years of research, with full proofs of some of the most remarkable achievements. Three main themes are evident: first, applications of étale cohomology; second, the Dipper-James theorems; finally, local representation theory.